Fiscal Efficiency and Public Service Innovation in the Era of Digitalization of Indonesian Government - Muh. Nur (PT. Anagata Sembagi Education, 2025)
This study examines how digital transformation influences fiscal efficiency and public service innovation in Indonesia by integrating global evidence with national policy analysis. Using a mixed method approach that combines conceptual frameworks with secondary data on Indonesia’s digital governance initiatives, the study finds that digital transformation contributes to fiscal optimization through administrative simplification, improved transparency, automated workflows and enhanced data integration. Innovations such as e procurement, online licensing and digital budgeting demonstrate measurable reductions in transaction costs and increased accountability in several regions. However, the effectiveness of these initiatives is constrained by structural barriers including unequal digital infrastructure, limited human resource capacity, fragmented interoperability, cultural resistance and inconsistent leadership commitment across administrative levels. Governance dynamics within Indonesia’s decentralized system produce variations in digital readiness, which in turn shape the extent of efficiency gains and service improvements. The study concludes that digital transformation can significantly enhance fiscal performance when supported by coordinated regulatory frameworks, strengthened institutional capacity, standardized data governance and sustained investment. These findings highlight the need for integrated national strategies that combine technological development with organizational reform to ensure inclusive and long term public sector modernization.